2021
DOI: 10.1002/lno.11990
|View full text |Cite
|
Sign up to set email alerts
|

Symbiotic stony and soft corals: Is their host‐algae relationship really mutualistic at lower mesophotic reefs?

Abstract: Mesophotic coral ecosystems (30-150 m depth) present a high oceanic biodiversity, but remain one of the most understudied reef habitats, especially below 60 m depth. Here, we have assessed the rates of photosynthesis and dissolved inorganic carbon (DIC) and nitrogen (DIN) assimilation by Symbiodiniaceae associated with four soft coral species of the genus Sinularia and two stony coral species of the genus Leptoseris collected respectively at 65 and 80-90 m depth in the Gulf of Eilat. Our study demonstrates tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 56 publications
0
23
0
1
Order By: Relevance
“…However, the provision of organic carbon is not the only important function attributed to the algal endosymbionts. Nitrogen is one of the primary growth-limiting nutrients in coral-reef ecosystems (2,6), and the algae have been thought to be the main contributors to nitrogen acquisition and recycling (7)(8)(9)(10)(11) due to their high capacity for ammonium assimilation (12). However, some evidence has also suggested an active role for the host in nitrogen assimilation (13), a view supported by the recent realization that the host also possesses the enzymatic machinery to recycle ammonium via the glutamine synthetase / glutamate synthase (GS/GOGAT) system (14)(15)(16).…”
mentioning
confidence: 99%
“…However, the provision of organic carbon is not the only important function attributed to the algal endosymbionts. Nitrogen is one of the primary growth-limiting nutrients in coral-reef ecosystems (2,6), and the algae have been thought to be the main contributors to nitrogen acquisition and recycling (7)(8)(9)(10)(11) due to their high capacity for ammonium assimilation (12). However, some evidence has also suggested an active role for the host in nitrogen assimilation (13), a view supported by the recent realization that the host also possesses the enzymatic machinery to recycle ammonium via the glutamine synthetase / glutamate synthase (GS/GOGAT) system (14)(15)(16).…”
mentioning
confidence: 99%
“…The results of our study demonstrate that surface‐brooding in the MCE population consistently lags behind that of the shallow one (Figures 2 and 4), which might also be due to the exponential reduction in light intensity with depth (Kahng et al, 2019). This lag in timing could result from the longer time needed to acquire the photosynthetically‐derived assimilates necessary for gonad development and maturation by corals in deeper habitats, compared with those inhabiting the well illuminated shallow depths (Ferrier‐Pagès et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Another aspect that may influence the vertical distribution of Orbicella species is their heterotrophic feeding capacity. It has been indicated that corals from deep environments increase their metabolic reliance on heterotrophy to compensate for reduced photosynthesis [ 53 , 54 ]. The dominance of O. franksi in deep environments might be related to an increased heterotrophic feeding capacity relative to its sibling species.…”
Section: Discussionmentioning
confidence: 99%